Colostrum silage: fermentative, microbiological and nutritional dynamics of colostrum fermented under anaerobic conditions at different temperatures - doi: 10.4025/actascianimsci.v35i4.19870 - Lucas Silveira Ferreira; Jackeline Thais Silva; Marília Ribeiro de Paula; Marcelo Cesar Soares; Carla Maris Machado Bittar (Acta Scientiarum. Animal Sciences, 2013)
The fermentative, microbiological and nutritional dynamics of bovine colostrum fermentedunder anaerobic conditions at different temperatures is provided. Colostrum was homogenized and stored inPET bottles in anaerobic conditions and incubated at controlled temperature (32.5 ± 1°C or 22.5 ± 1°C) or atroom temperature (17.4 - 21.5ºC) and opened after 0, 1, 7, 14, 21, 28 and 35 days to determine fermentative andnutritional parameters and bacteria, yeast and mold counts. Further, pH rates showed significant variationsduring the fermentation period (p < 0.0001), with colostrum stored at 32.5°C, exhibiting the lowest rates andsignificant reduction during the first days. Titratable acidity and lactic acid concentration showed increasing ratesand LAB development was intense, especially at high temperatures. After 35 days, about 50% of total nitrogenbecame non-protein N and casein fraction was reduced to 0.66% of total nitrogen. Lactose decreased duringfermentation and fat concentrations were not affected by temperature. Results suggested that the temperature atwhich the colostrum was fermented directly influenced the speed and intensity of microbial populationdevelopment and degradation of the main nutritional parameters, such as casein and lactose